Peningkatan Kemampuan Berpikir Kreatif dengan Konteks Budaya Lokal Karawang Menggunakan Realistic Mathematics Education Pada Masa Pandemi - Asmara, Andes Safarandes; Fitri, Ayu; Anwar, Aang Solahudin; Muhtarulloh, Fahrudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
Creative thinking can be said to construct an idea that emphasizes several aspects of ability, such as flexibility and originality. This can familiarize students not only with knowing the material but also understanding and applying it in everyday life so that understanding becomes long-term memory in memory. This creative thinking ability can be facilitated during the learning process in a mathematically realistic approach or better known as RME. So the purpose of this research is to improve students' creative abilities through a mathematical realistic approach with local culture as a context. This study uses a quasi-experimental method with a research design of The Nonequivalent Control Group Design through a creative thinking test. The study was conducted in two classes with different treatments, one class as the experimental class and the other as the control class. Conducted at the seventh grade junior high school level. The results of this study are the improvement of students' mathematical creative thinking skills who receive RME learning is better than students who receive expository learning methods.